Redução da duração do trabalho como mecanismo de aumento da empregabilidade: necessária limitação à flexibilização da jornada de trabalho? - Dantas, Iana Melo Solano (2016)
The study aims to examine the relationship between the reduction of the working day and promoting employability, from a discussion of the necessary limitation of the flexibility of working hours. Although the working hours issue is recurrent in labor harvest, concern about it has been changing with the passage of time. In the late twentieth century, when the main problem in developed economies becomes unemployment, the discussion on the reduction of the working day takes on new meaning. The reduction of working hours around the center of the debate as a means of generating new jobs. In an attempt to address the structural and cyclical causes of unemployment, neoliberal ideology presents the flexibility of labor standards as a solution, by setting up a so-called single thought of hegemony of this model. To address the problem raised by this research: the reduction of working hours would be a mechanism capable of generating new jobs, the hypothesis presented goes against the neoliberal ideology attributed to flexibility, in that it believes that the reduction of journey work can influence the creation of new jobs, since the flexibility of working hours to be limited and not encouraged. Such limitations must be embodied in two mechanisms: limiting the use of overtime, with a consequent increase in the additional overtime and end of the hour bank of the institute. The research aims to demonstrate the arguments that justify the need to adopt such measures in case of reduction of working hours in Brazil through the deductive method of approach, the hermeneutic procedures, comparative and historical and bibliographical research technique.